A comparative review of effect of ultrasonic shot peening on LCF behavior of the alloys - Muhammad Syamim, Mazlan; Mohamad Rusydi, Mohamad Yasin (Institution of Engineering and Technology, 2022)
The low cycle fatigue (LCF) behaviour of AA7075, AA2014, and austenitic stainless steel was studied in relation to ultrasonic shot peening (USSP) treatment, with all three materials sharing nearly identical parameters for ultrasonic shot peening treatments of varying durations. Ultrasonic shot peening is a recent method for causing high plastic deformation on the surface of materials. Nanosized grains develop on the surface of the materials as a result of the procedure. If performed correctly, ultrasonic shot peening can be observed in some tests to increase the surface hardness and fatigue resistance of the material to which it is applied. In this research, the effects of USSP on various materials are compared. The LCF life of AA7075 has enhanced by 54 percent thanks to the low strain amplitude. Both AA2014 and austenitic stainless steel have demonstrated that, when subjected to low strain amplitude, there is an improvement in LCF life as well as a delay in fatigue fracture on the material.